Legal regulation of foreign investments in industry avitsiyniy (economic and legal aspects) - Заболотній, Сергій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
This article examines the legal aspects of foreign investment in the aviation industry, and identifies ways to address the development areas of the industry.